PENGARUH MODAL KERJA TERHADAP ROA dan ROE DI PT PERTAMINA (PERSERO) TBK 2020–2024 - Zahira Syifa Nurpatimah; Puji Isyanto (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
This research investigates how significantly working capital contributes to the financial performance of a company, with a focus on PT Pertamina (Persero) Tbk during the 2020–2024 period. The company’s profitability is evaluated using two primary metrics: Return on Assets (ROA) and Return on Equity (ROE). Employing a descriptive quantitative method, the study relies on secondary data obtained from the firm's annual financial statements published on the Indonesia Stock Exchange. Data analysis was conducted using multiple linear regression via SPSS version 16.0The findings show that working capital significantly affects both ROA and ROE. The determination coefficient (R²) demonstrates that variations in ROA and ROE can be explained by working capital at 83.2% and 85%, respectively. Results from the F-test indicate that working capital jointly impacts profitability in a statistically meaningful way. However, the T-test results show a negative influence, implying that poor or excessive utilization of working capital may reduce profitability levels.In conclusion, companies must effectively and wisely manage their working capital to ensure continued improvement and stability in their financial outcomes.